Respon Tanah dan Tanaman Kacang Tanah (Arachis hypogaea L.) pada Pemberian Beberapa Jenis Mikroorganisme Lokal (MOL) dan Pupuk Kandang - Elisabeth Sri Pujiastuti; Ferlist Rio Siahaan; Yanto Raya Tampubolon; Juli Ritha Tarigan; Susana Tabah Trina Sumihar (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2021)
Introduction: This research was conducted to determine the effect of several types of local microorganism solutions and manures on the growth and yield of peanut and their impact on the physical properties of ultisols. Materials and Methods: The researches was conducted in Simalingkar B, Medan using Factorial Randomized Block Design within three replications. The first factor was types of microbe sources of local microbial solutions, include un-treated waste (M0), pineapple (M1), orange (M2), and tamarillo (M3) wastes. The second factor was manure types, inluce un-treated manure (P0), chicken (P1), cow (P2), and goat (P3) manures. The parameters were: soil physical characteristics (bulk density, water content and total of pore space), plant height, stem diameter, number of pods, and dry seeds yield. Results: The types of local microorganism solutions only affect to plant height of peanut, but has insignificant effect on the physical properties of ultisols, and stem diameter, the number of filled pods.plant-1, and the dry seeds yield.ha-1 of peanut. The types of manure had significantly effected on plant height and number of filled pods.plant-1, but had insignificant effect on stem diameter, dry seeds yield.ha-1 and the physical properties of ultisols. The interaction of MOL sources and manure did not significantly affect the growth and yield of peanut as well as the physical properties of ultisols. Orange MOL and chicken manure could be increase the plant height of peanut by 18.61% and 6.75%, respectively, compared to un-treated. Goat manure showed the highest number of pods.plant-1 by 6.32% compared to un-treated.